Honeyd untuk Mendeteksi Serangan Jaringan di Universitas Muhammadiyah Purwokerto - Harjono Harjono; Agung Purwo Wicaksono (JUITA : Jurnal Informatika, 2013)
Computer network technology is a necessity that must be applied by any organization at this time. But the connection of computers to each other can be exploited by certain parties to carry out the attack in order to obtain personal gain. This research aimed to detect attacks in the network of Muhammadiyah University of Purwokerto using Honeyd. Honeyd is placed on the internal network segment, with the configuration to mimic the four host operating systems and different services. A number of attacks to Honeyd originated from several host with private IP address of the internal network. Attacks are detected done automatically by malware